2013
DOI: 10.1002/ggge.20141
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and calibration of nonheating paleointensity methods: A case study using dusty olivine

Abstract: [1] We present a comparative study of nonheating paleointensity methods, with the aim of determining the optimum method for obtaining paleointensities from ''dusty olivine'' in chondritic meteorites. The REM method, whereby thermoremanent magnetization (TRM) is normalized by saturation isothermal remanent magnetization (SIRM), is shown to ''over normalize'' TRM in dusty olivine due to the transformation of stable single-vortex (SV) states to metastable single-domain (SD) states in a saturating field. The probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(72 citation statements)
references
References 38 publications
3
68
1
Order By: Relevance
“…Finally, our applied bias field of 100 µT for the ARM acquisition experiments is well within the range where ARM intensity varies linearly with the bias field. For these reasons, we expect similar performance of the ARM normalization method for our dusty olivinebearing chondrules compared to the SV grains dominated synthetic dusty olivine grains used by Lappe et al (29), implying that 1σ uncertainty due to the ARM calibration factor is ~20%.…”
Section: Calculation Of Paleointensitiessupporting
confidence: 57%
See 3 more Smart Citations
“…Finally, our applied bias field of 100 µT for the ARM acquisition experiments is well within the range where ARM intensity varies linearly with the bias field. For these reasons, we expect similar performance of the ARM normalization method for our dusty olivinebearing chondrules compared to the SV grains dominated synthetic dusty olivine grains used by Lappe et al (29), implying that 1σ uncertainty due to the ARM calibration factor is ~20%.…”
Section: Calculation Of Paleointensitiessupporting
confidence: 57%
“…The high coercivities above 170 mT indicate that SD kamacite grains are responsible for carrying part of the HC magnetizations (29). The field geometry observed in SQUID Microscope and NV diamond magnetometer maps confirm that high coercivity magnetization is carried by dusty olivine grains (Fig.…”
Section: The Hc/ht Componentmentioning
confidence: 58%
See 2 more Smart Citations
“…For example, Pike and Fernandez [] studied submicron Co dots and suggested that the magnetic vortex state should give rise to two positive regions and a possible extra butterfly pattern in FORC diagrams. However, these features have only been observed so far in synthetic samples with a narrow grain‐size range [ Pike and Fernandez , ; Dumas et al , , ; Lappe et al , , ] and in low‐temperature FORC measurements [ Smirnov , , ; Carvallo and Muxworthy , ]. Hysteresis mechanisms in multidomain (MD) samples have also been analyzed using FORC diagrams [ Pike et al , ], and it has been concluded that the classical domain wall pinning model of Néel [] does not explain the behavior of natural MD samples.…”
Section: Introductionmentioning
confidence: 99%